2011
DOI: 10.1093/humrep/der181
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a levonorgestrel enteric-coated tablet as an over-the-counter drug for emergency contraception: a Phase IV clinical trial

Abstract: BACKGROUNDAn enteric-coated levonorgestrel emergency contraceptive pill (E-LNG-ECP) is an improved formulation, in terms of side effects, which both dissolves and is absorbed in the intestine. Our aim was to evaluate the efficacy and safety of E-LNG-ECP as an over-the-counter (OTC) drug for emergency contraception (EC) in Chinese women.METHODSA Phase IV clinical trial was conducted in five family planning clinics in China. Women seeking EC within 72 h after unprotected sexual intercourse or contraceptive failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Globally, emergency contraception pills (ECPs) are widely used by women after unprotected intercourse to prevent unwanted pregnancies [1]. In many countries including Kenya; most pharmacies stock Levonorgestrel-only pills for emergency contraception (LNG-EC) and sell them over-the-counter form [2-5]. LNG-EC can prevent unwanted pregnancies with an efficacy of 52-94% when used within 12 hours of unprotected intercourse [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, emergency contraception pills (ECPs) are widely used by women after unprotected intercourse to prevent unwanted pregnancies [1]. In many countries including Kenya; most pharmacies stock Levonorgestrel-only pills for emergency contraception (LNG-EC) and sell them over-the-counter form [2-5]. LNG-EC can prevent unwanted pregnancies with an efficacy of 52-94% when used within 12 hours of unprotected intercourse [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…The 12-month postinsertion continuation rate was 94.0 per 100 woman-years 14 . An enteric-coated levonorgestrel emergency contraceptive pill (E-LNG-ECP) is an improved formulation, in terms of side effects, which is both dissolved and absorbed in the intestine 15 .…”
Section: Types Of Emergency Contraceptive Pills (Ecps)mentioning
confidence: 99%
“…In a large‐scale study, the World Health Organization reported that the levonorgestrel regimen (0.75 mg, repeated 12 h later) was better tolerated, more effective, and caused fewer side effects, such as nausea and vomiting than the Yuzpe regimen (ethinylestradiol 100 μg plus levonorgestrel 0.5 mg, repeated 12 h later) . Levonorgestrel (two 0.75 mg doses 12 h apart) prescription was approved as an emergency contraceptive method in the United States in 1999 and has been marketed in many countries, and the same regimen was subsequently approved as an over‐the‐counter drug in 2006. It was shown in 2002 that a single 1.5 mg oral levonorgestrel dose within 72 h of sexual intercourse could substitute for two 0.75 mg doses 12 h apart, and this new regimen was approved as an over‐the‐counter treatment in the United States in 2013.…”
Section: Introductionmentioning
confidence: 99%